Homotopic Classification of Euler-Lagrange Systems - Habre, Samer S. (2002)
In this paper we examine the linear elliptic partial differential operators that appear as Euler-Lagrange systems of certain variational integrals. We give a sufficient condition for those systems to be deformable to the Laplace system.